Socialization and Training on Organic Waste Processing to Make Eco-enzymes and their Derivative Products - Dewi Meidalima; Ruarita Ramadhalina Kawaty; Karlin Agustina; Chuzaimah Chuzaimah; Reshi Wahyuni (Universitas Muhammadiyah Palembang, 2023)
Waste, both organic and inorganic, has become a global problem. Waste generated from kitchen activities, such as leftover vegetables and fruit, contributes significantly to the waste problem. This community service activity aims to train people in Sungsang IV Village, Banyuasin II Distric, Banyuasin Regency, to process vegetable and fruit waste resulting from kitchen activities to be eco-enzymes and their derivative products. Activities are carried out for 3 months, starting from initial preparation of situation and needs analysis. Implementation in the field involves socialization and training methods for making eco-enzymes and their derivative products in the form of soap and fertilizer. As a result of this activity, the people of Sungsang IV Village succeeded in making 50 liters of eco enzymes and 20 liters of liquid soap. In this activity, the community was also given training to use eco-enzymes as fertilizer. Training participants are taught to grow organic vegetables in their home yards by using eco-enzymes. The people in Sungsang IV village have a high curiosity about new and positive things. They enthusiastically took part in the training and as a result, on October 7, 2023, they participated in an exhibition for MSMEs making eco-enzymes and their derivative products. The Exhibition was organized by the Banyuasin Regency Government.